Systematic Review of the Economics of School-Based Interventions for Dating Violence and Gender-Based Violence. (June 2023) - Kiff, Fraizer; Shaw, Naomi; Orr, Noreen; Rizzo, Andrew. J.; Chollet, Annah; Young, Honor; Rigby, Emma; Hagell, Ann; Berry, Vashti; Bonell, Chris; Melendez-Torres, G. J.; Farmer, Caroline
Dating and relationship violence (DRV) and gender-based violence (GBV) among children and young people incur a high cost to individuals and society. School-based interventions present an opportunity to prevent DRV and GBV early in individuals' lives. However, with school resources under pressure, policymakers require guidance on the economics of implementing interventions. As part of a large systematic review funded by the National Institute for Health and Care Research (NIHR), we searched for economic evaluations and costing studies of school-based interventions for DRV and GBV. No formal economic evaluations were identified. Seven studies reporting costs, cost savings, or resource use for eight interventions were identified. The largest costs of implementing interventions were related to staff training and salaries but savings could be made by implementing interventions on a large scale. The potential cost savings of avoided DRV and GBV far outweighed the costs of implementation.